Հայրավանքի գրչության կենտրոնը - Ղազարոսյան, Արփենիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Айраванк известен также как монастырь отца Иоанна, монастырь Айриванк, Мардагавнеатс Сурб Ншан. Это один из самых известных монастырей Гегаркуникской области. В источниках нет сведений о строительстве монастырского комплекса, о культурной деятельности монахов. Впервые этот монастырь упоминается в колофонах 1530 года. Сейчас от монастырского комплекса сохранились только церковь и притвор, архитектура и литографии которого изучены. В статье мы даем новое прочтение литографии. Также изучены названия монастыря, особенно имя Мардагавняц Сурб Ншан, о котором есть свидетельства в колофонах, а также известна одна легенда. Hayravank is also known as Monastery of Father Hovhannes, Ayrivank Monastery, Mardagavneats St. Neshan (Holy Cross) Monastery. This is one of the most famous monasteries of Gegharkunik. The sources do not contain information about the construction of the monastic complex; there is no information about the cultural activities of monks, either. This monastery was first mentioned in colophons of 1530. Now only the church and the narthex have survived from the monastic complex, the architecture and lithographs of which have been studied. In this article, we present a new lithographic decrypt. We have also studied the names of the monastery, especially the name Mardagavneats St. Neshan, about which there is a legend and evidence in the colophons․
Keywords: Հայոց պատմություն; Հայ մշակույթ